Experimental investigation of perfobond hoop shear connector's bearing capacity and slip. (1st November 2019) - Li, Xiao; Hu, Zhijian; Fan, Liang; Shah, Yasir Ibrahim
Highlights: Push-out tests on PBH are conducted. Shear-friction theory is employed. A simplified formula for PBH bearing capacity is proposed. The slip value for service and ultimate design are proposed. Abstract: Perfobond hoop (PBH) is a type of shear connector specifically promoted from perforated steel plate connectors (PBL) with relatively higher bearing capacity and ductility. However, there is limited information on the effect of the parameters on PBH's bearing capacity and slip, such as concrete compressive strength, opening diameter on perfobond plate and hoop diameter. To investigate the mechanical behavior of PBH, push-out tests were conducted under static loading. Corresponding failure modes, bearing capacity and load-slip relationship were obtained. In this paper, the shear-friction theory and the method of multivariate linear regression analysis are employed to analyze the experimental results and a simplified formula for PBH bearing capacity is proposed based on the test results of eighteen specimens. By fitting the normalized results of specimens, an empirical equation for the load-slip relationship of PBH within the whole loading process is obtained, which is in an exponential form. The proposed formulae are both validated with the verification results and can provide good references for the design and applications of PBH.